2021
DOI: 10.1111/cea.13880
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to COVID‐19 vaccines: A practical approach

Abstract: According to the World Health Organization by the 27 March 2021, there have been 125 781 957 confirmed cases of COVID-19 (SARS-CoV-2), including 2,759,432 deaths. 1 COVID-19-related mortality is substantial (2% overall) and higher in high-risk individuals (>10%).Current treatment options are limited. Trials and real-life experience confirm that COVID-19 vaccines drastically reduce the severity of COVID infections, prevent deaths and curb the spread of the pandemic. 2 As of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 30 publications
(57 reference statements)
3
41
0
3
Order By: Relevance
“…Consistent with previous studies, our review found that foods, drugs or therapeutic agents, contrast media, stinging insects or jellyfish, cosmetics, detergents, household products, and latex are the most common triggers of anaphylactic and nonanaphylactic reactions induced by mRNA COVID-19 vaccines [ 21 23 , 38 , 46 ]. Previous history of anaphylaxis; and comorbidities such as asthma, allergic rhinitis, atopic and contact eczema/dermatitis and psoriasis and cholinergic urticaria were also described by other investigators as elicitors for anaphylactic and nonanaphylactic reactions to mRNA COVID-19 vaccines [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies, our review found that foods, drugs or therapeutic agents, contrast media, stinging insects or jellyfish, cosmetics, detergents, household products, and latex are the most common triggers of anaphylactic and nonanaphylactic reactions induced by mRNA COVID-19 vaccines [ 21 23 , 38 , 46 ]. Previous history of anaphylaxis; and comorbidities such as asthma, allergic rhinitis, atopic and contact eczema/dermatitis and psoriasis and cholinergic urticaria were also described by other investigators as elicitors for anaphylactic and nonanaphylactic reactions to mRNA COVID-19 vaccines [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 89%
“… 22 , 23 , 29 Additionally, PEG‐ASNase and BNT162b2 contain PEG of differing molecular weight; allergenicity correlates with molecular weight. 24 , 28 , 29 , 30 To the best of our knowledge, there have been no allergic reactions to BNT162b2 in patients with PEG‐ASNase allergy.…”
Section: Discussionmentioning
confidence: 92%
“…This is because some patients labeled as PEG‐ASNase allergic are sensitized to the asparaginase component and not the PEG‐moiety 22,23,29 . Additionally, PEG‐ASNase and BNT162b2 contain PEG of differing molecular weight; allergenicity correlates with molecular weight 24,28–30 . To the best of our knowledge, there have been no allergic reactions to BNT162b2 in patients with PEG‐ASNase allergy.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, mRNA and viral vector vaccines activate different TLRs; therefore, immunological differences appear plausible [36,37]. Moreover, vaccines comprise various molecules that potentially act as haptens to elicit type IV allergic reactions [38]. At this point, it is not clear whether specific vaccine types impose a larger risk for severe cutaneous ADRs to specific groups of patients, e.g., psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%